2011
DOI: 10.1016/j.ijgo.2011.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing women's willingness to collect their own cervical samples for HPV testing as part of the ASPIRE cervical cancer screening project in Uganda

Abstract: Self-collection is an option in impoverished settings in Africa. To improve acceptability, women should be taught how to properly collect their own cervical sample and encouraged to find ways to make the collection less embarrassing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 17 publications
8
103
4
Order By: Relevance
“…The top concerns found in the present study are consistent with findings from previous research in multiple settings suggesting that women may be concerned about pain or injury,15 34 35 failing to self-collect an adequate sample, and the reliability or accuracy of a self-collected sample compared to one collected by a clinician 15 35 36. Programmes implementing self-collected samples may be able to address these concerns.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The top concerns found in the present study are consistent with findings from previous research in multiple settings suggesting that women may be concerned about pain or injury,15 34 35 failing to self-collect an adequate sample, and the reliability or accuracy of a self-collected sample compared to one collected by a clinician 15 35 36. Programmes implementing self-collected samples may be able to address these concerns.…”
Section: Discussionsupporting
confidence: 88%
“…Qualitative research among Malawian women found that cervical cancer knowledge was limited and thus this may be an important place to intervene to increase screening 33. In line with our findings on the importance of perceived behavioural control, a study among urban Ugandan women that also utilised the TPB similarly found that perceived behavioural control was associated with increased willingness to self-collect,34 thus screening programmes may benefit from building women's skills and confidence in their ability to self-collect samples.…”
Section: Discussionsupporting
confidence: 84%
“…Until now, this collaboration has conducted a baseline survey to explore the acceptability of self-collected HPV DNA testing and attitudes towards cervical cancer screening26 27 as well as a feasibility study enrolling 200 women and taking them from HPV swab self-collection to colposcopy and treatment 28…”
Section: Context and Settingmentioning
confidence: 99%
“…HPV testing has been suggested as primary screening in place of cytology in the US and Europe (Kitchener et al 2009;Cusick et al 2006) and a negative HPV test predicts a less than 2% risk of developing cervical dysplasia (Naucler et al 2009;Lonky et al 2010;Mesher et al 2010;Kitchener et al 2009;Cusick et al 2006). An advantage of HPV testing is that a pelvic exam is not required, but simply insertion of a swab into the vagina to obtain the sample; furthermore, studies have shown that accurate results can be obtained with self-testing, where the woman inserts the swab into her own vagina (Ogilvie et al 2005;Balasubramanian et al 2010), that this compares favorably to collection by clinicians (Bhatla et al 2009;Petignat et al 2007) and is acceptable to women (Mitchell et al 2011;Lack et al 2005). However, treatment of positive results clearly requires access to and good visualization of the cervix.…”
Section: Alternatives To Cervical Cytologymentioning
confidence: 99%
“…An advantage of HPV testing is that pelvic exam is not required, but simply insertion of a swab into the vagina to obtain the sample; furthermore, studies have shown that accurate results can be obtained with self-testing, where the woman insert the swab into her own vagina (Ogilvie et al 2005;Balasubramanian et al 2010), that this compares favorably to collection by clinicians (Bhatla et al 2009;Petignat et al 2007) and is acceptable to women (Mitchell et al 2011;Lack et al 2005). However, treatment of positive results clearly requires access to and good visualization of the cervix.…”
Section: Alternatives To Cervical Cytologymentioning
confidence: 99%